Obstetric violence in the case law of the Inter-American Court of Human Rights - Valverde Caman, Fernando (2021)
This paper aims to analyze the existing problem of obstetric violence, linked to gender-based violence, against women during pregnancy and childbirth. To this end, different international cases tried by the Inter-American Human Rights System will be analyzed. This system has issued various decisions establishing the liability of states for the violation of women’s human rights. Likewise, it has issued recommendations to the states on measures to better protect women and to not incur in this type of violence against them.